(untitled) - UNFPA Vietnam (Ha Noi, 2007)
This publication is the third report in the series of lessons learnt and best practices in reproductive health supported by UNFPA in 2007. The report documents changing patterns of reproductive health knowledge and behaviour of the ethnic minority community in mountainous provinces. It was published in both English and Vietnamese
Keywords: Health services,Maternal health services,Dịch vụ chăm sóc sức khỏe bà mẹ,Chăm sóc sức khỏe; Vietnam,Việt Nam